New sponge species from Seno Magdalena, Puyuhuapi Fjord and Jacaf Canal (Chile) - Bertolino, Marco; Costa, Gabriele; Bavestrello, Giorgio; Pansini, Maurizio; Daneri, Giovanni (European Journal of Taxonomy, 2020)
Until now, only 177 species of sponges (Porifera) have been reported for Chilean coastal waters. Here we describe recent scuba diving surveys undertaken to improve our knowledge of the diversity of the sponge fauna of the Seno Magdalena, Puyuhuapi Fjord and Jacaf Canal in Chilean Patagonia. Despite these relatively harsh environments, our study yielded 23 species of Demospongiae, nine of which are new to science and described here: Hymerabdia imperfecta Bertolino, Costa & Pansini sp. nov., Axinella cylindrica Bertolino, Costa & Pansini sp. nov., Axinella coronata Bertolino, Costa & Pansini sp. nov., Biemna aurantiaca Bertolino, Costa & Pansini sp. nov., Biemna erecta Bertolino, Costa & Pansini sp. nov., Biemna typica Bertolino, Costa & Pansini sp. nov., Scopalina cribrosa Bertolino, Costa & Pansini sp. nov., Rhizaxinella strongylata Bertolino, Costa & Pansini sp. nov. and Darwinella pronzatoi Bertolino, Costa & Pansini sp. nov. One species, Hymedesmia (Stylopus) lissostyla (Bergquist & Fromont, 1988), is reported for the first time for Chile.